-4(r-7)+5=-9-6(r-10)

Simple and best practice solution for -4(r-7)+5=-9-6(r-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(r-7)+5=-9-6(r-10) equation:



-4(r-7)+5=-9-6(r-10)
We move all terms to the left:
-4(r-7)+5-(-9-6(r-10))=0
We multiply parentheses
-4r-(-9-6(r-10))+28+5=0
We calculate terms in parentheses: -(-9-6(r-10)), so:
-9-6(r-10)
determiningTheFunctionDomain -6(r-10)-9
We multiply parentheses
-6r+60-9
We add all the numbers together, and all the variables
-6r+51
Back to the equation:
-(-6r+51)
We add all the numbers together, and all the variables
-4r-(-6r+51)+33=0
We get rid of parentheses
-4r+6r-51+33=0
We add all the numbers together, and all the variables
2r-18=0
We move all terms containing r to the left, all other terms to the right
2r=18
r=18/2
r=9

See similar equations:

| 67-w=179 | | x+109=x=89 | | -9s-17=-12s+13 | | 4y+2=8y–(6y–10) | | 123=-3(-2+5n)-3 | | -5+5x=7x-27 | | 10=x+7+x | | -5(x+8)=-(2x+7) | | 8(2n+4)=-96 | | -5(5y-6)-y=-2(y-3) | | 70+35x=100+25x | | x+5/x-6=0 | | -8u+13=-11u-11-5u | | 120=4(6-3x) | | 2x-6+x+7=25+x | | -5(x-3)+6x=-(x+5)+6 | | 50x+-14,040=20x+12,500 | | -3m+6(2-5m)=144 | | -3x-4+7=21 | | 70+35x=100+25x* | | -8u+13=-11u−11−5u | | 4x-133=47 | | 50+9.99m=25+14.99m | | -6x+5(6x-5)=-121 | | -12(n+10)+n=9n-8(n-9) | | -14=1+n-6n | | -5(1+6n)=-185 | | 50x+14,040=20x+12,500 | | 10−6p=3p−5. | | -7(2-8b)=-238 | | 8x-16=76 | | 50x+14,040=12,500+20x |

Equations solver categories